Thriving and spirituality among youth : research perspectives and future possibilities - Warren, Amy Eva Alberts; Lerner, Richard M.; Phelps, Erin. (Hoboken, N.J. : John Wiley & Sons, 2011)
'Thriving and Spirituality Among Youth empirically explores the connections between spirituality and positive youth development through the research of a set of scholars from the wide array of scientific fields including biology, sociology, and theology. This unique handbook shows how to foster positive development during adolescence, including youth contributions to families and communities in civil society. The material draws on research conducted with various populations including immigrant Hispanic, Chinese, Israeli, and Muslim-American youth. Social workers and mental health professionals will find a new, developmentally rigorous data base for a science of'adolescent spirituality.''--
Includes index.
Keywords: Youth -- Religious life; Mental health -- Religious aspects; Well-being -- Religious aspects; Adolescent psychology; Developmental psychology -- Religious aspects